The scenario of childhood blindness and its remedy in Nepal (Journal of Patan Academy of Health Sciences, 2021)
Childhood blindness represents one of the most common disabling and for children. There are approximately 1.4 million blind children worldwide and two-thirds live in the developing countries like Nepal. In Nepal more than 80% of the causes of childhood blindness are preventable. The main causes of blindness are diseases related to cornea, retina, lens optic nerve, refractive errors, amblyopia and hereditary. Most of the cases of unilateral childhood blindness are due to corneal causes. To decrease the burden of blindness, awareness program about various ocular diseases, nutritional blindness, ocular trauma, refractive errors, strabismus and amblyopia should be provided to the community health workers and parents. School screening programs and free eye camps should be conducted and motivate the community for regular eye checkup and follow up. Eye services should reach to rural areas and for poor socio-economic condition. Eye health education should focus on proper nutrition of children and harmful effects of traditional eye medicines. The objective of this study was to investigate the magnitude of childhood blindness in Nepal along with their possible causes. Similarly, this study is aimed to highlight the best possible modalities for the remedy of childhood blindness in the developing countries like Nepal.